BOUND MORPHEME ANALYSIS OF TWITTER TRENDS ABOUT KAKAO M ISSUE - Irene Kendy Amalia (Faculty of Education and Teachers Training, 2021)
Morphemes are the smallest part of languages that forms a word or sentence. Morphemes are root words or affixes that build a new word with a detailed meaning or new meaning. In linguistic, morphemes small part that is important to make a meaningful sentence both literally and figuratively. There are many kinds of morphemes, one of them is bound morpheme. In social media, especially Twitter, which emphasizes authorship and reading content, bound morphemes are vital to building posts or threads. Many posts or threads from this platform show us the issues in our country or around the world. More often, the issues discussed by Twitter users faster becomes a trending topic in search pages and bars. For example, a few days ago, there were controversies between two music platforms and companies. Kakao M and Spotify. This two platform does something controversial and makes them as one of trending topics in worldwide. In the posts, it contains so many morphemes that build the words and threads. Especially the bound morpheme.